Developing Android-Digibook with Project-Based Learning Model on Research Method Subject in Guidance and Counselling Department of Medan State University - Albert Pauli Sirait (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to create a digital textbook based on project based Learning Model in research methods Subject. The research using the ADDIE model. The development stage is the stage of manufacture of digibook android-based in accordance with the design plan. Media experts give excellent ratings for throughout the item with the total amount of 82.50 with an average value is 4.10. This application is tested on 30 students of the 1st half of Guidance and Counseling Department of the Faculty of Education Unimed. The results of calculations throughout the student questionnaire responses obtained 87.15%% percentage of aspects of good feelings, 86.57% of the student's interest aspects of the use of the application, 85.85% of aspects of attention, and 88.24% of aspects of student involvement.